SISTEM INFORMASI PENJUALAN SPAREPART DAN JOK SEPEDA MOTOR PADA BENGKEL RAKYAT MOTOR BERBASIS WEB - Sakti Simangunsong; Marlyna Infryanty Hutapea; Eva Julia G. Harianja (Universitas Methodist Indonesia, 2022)
Bengkel Rakyat Motor isda businessdthat is engaged in the business of selling spare parts, motorcycle seats and motorcycle repairs. The workshop has quite a number of customers who come to buy various kinds of motorcycle spare parts. However, the workshop still uses manual methods in the data processing process, such as compiling spare parts data which includes spare parts prices, spare parts stocks are still recorded in the ledger. This often causes problems such as loss of sales data which causes re-recording so that the resulting report is not perfect. Therefore, we need a web programming system that functions to make it easier for Bengkel Rakyat Motor owners to solve problems that occur, such as sales of goods, stock of goods, and prices of goods which are still done manually.